Validation of wind turbine wake models with focus on the dynamic wake meandering model - Inga Reinwardt and Nils Gerke and Peter Dalhoff and Dirk Steudel and Wolfgang Moser (Journal of physics / Conference Series, 2018)
This analysis compares current wake models, such as the Sten Frandsen turbulence model, an engineering wind speed deficit and turbulence model developed by G. Chr. Larsen, the N. O. Jensen wind speed deficit description and three variations of the dynamic wake meandering (DWM) model to measurements from onshore wind farms. Special attention is given to the dynamic wake meandering model. Today different versions or implementations of the dynamic wake meandering model exist. These versions differ among others in the calculation of the quasi-steady wake deficit in the meandering frame of reference. The influence of these calculation methods on loads and yield is analysed in this work. The validation of the mentioned wake models is based on turbine load, power and wind measurements from two onshore wind farms. One key result of this work is that the DWM model in most cases coincides superiorly with the measurement results compared to the other engineering wake models commonly used in industry.